2021
DOI: 10.3390/biomedicines9060610
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Blockade of PPARα Exacerbates Inflammatory Pain-Related Impairment of Spatial Memory in Rats

Abstract: Peroxisome proliferator-activated receptors (PPARs) are ligand-dependent transcription factors that exist in three isoforms: PPARα, PPARβ/δ and PPARγ. Studies suggest that the PPAR signalling system may modulate pain, anxiety and cognition. The aim of the present study was to investigate whether endogenous signalling via PPARs differentially modulates innate anxiety responses and mnemonic function in the presence and absence of inflammatory pain. We examined the effects of intraperitoneal administration of GW6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 103 publications
(135 reference statements)
0
11
0
Order By: Relevance
“…The same remarks suggesting an effect of PEA in rescuing memory deficits and injured hippocampal neurons, possibly by exerting anti-inflammatory and neuroprotective effects, were reported in preclinical models of VaD ( 36 , 42 ). Finally, converging evidence for an improving effect of PEA administration on learning and memory and their biological underpinnings was also found in the context of brain ischemia reperfusion injury ( 24 ), PD ( 39 ), SNI ( 40 , 41 , 49 ), TBI ( 28 ), CFA ( 51 ), and high-fat diet ( 48 ), where cognitive decline is a common complication of the disease.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The same remarks suggesting an effect of PEA in rescuing memory deficits and injured hippocampal neurons, possibly by exerting anti-inflammatory and neuroprotective effects, were reported in preclinical models of VaD ( 36 , 42 ). Finally, converging evidence for an improving effect of PEA administration on learning and memory and their biological underpinnings was also found in the context of brain ischemia reperfusion injury ( 24 ), PD ( 39 ), SNI ( 40 , 41 , 49 ), TBI ( 28 ), CFA ( 51 ), and high-fat diet ( 48 ), where cognitive decline is a common complication of the disease.…”
Section: Resultsmentioning
confidence: 94%
“…Most evidence regarding a potential therapeutic effect of PEA in NCDs was gathered from preclinical studies administering the compound to animal models of NCDs ( Table 1B ), including AD ( 20 , 31 , 38 , 46 , 47 , 50 ), Aβ-exposed ( 34 ), middle cerebral artery occlusion (MCAo) ( 24 ), PD ( 39 ), vascular dementia (VaD) ( 36 , 42 ), spared nerve injury (SNI) ( 40 , 41 , 49 ), TBI ( 28 ), Complete Freund's Adjuvant (CFA) ( 51 ), and high-fat diet ( 48 ) models. Despite the evidence of similar methodologies across the reviewed studies, a certain heterogeneity was found in terms of animal type [mice ( 20 , 28 , 31 , 36 , 38 42 , 46 , 48 50 ), rat ( 24 , 34 , 47 , 51 )], period of exposure [from 4 to 5 weeks old to 21 months old), PEA formulation [alone unspecified, PEA ( 31 , 34 , 50 , 51 ); alone micronized, PEAm ( 39 ); alone ultra-micronized, um-PEA ( 20 , 38 , 40 , 41 , 46 , 48 ); combined with oxazoline, PEA-OXA ( 42 , 49 ); combined with luteolin, PEALut ( 24 , 28 , 36 , 47 )], PEA mode of administration [intraperitoneal ( 34 , 40 , 41 , 47 , 49 , 51 ), subcutaneous ( 20 , 31 , 38 ), oral ( 24 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have pointed to a possible role of PPARs in anxiety and cognition. Our recent work has shown that the administration of a PPARα antagonist exacerbated inflammatory pain-related impairment of spatial memory in rats [ 57 ]. Youssef et al (2019) showed that the administration of a PPARγ antagonist blocked the anxiolytic effect of beta-caryophyllene.…”
Section: Discussionmentioning
confidence: 99%
“…They are present at key peripheral, spinal, and supraspinal sites involved in pain processing [ 27 ], and the increase in PPARs activation or protein expression in the spinal cord has been demonstrated in several animal models of chronic pain [ 28 ]. Indeed, several studies suggested that their pharmacological manipulation could represent a promising therapeutic strategy in the control of different types of neuropathic pain [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%